2020
DOI: 10.3390/geosciences10040143
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Natural Beachrock and Physical–Mechanical Comparison with Artificial Beachrock Induced by MICP as a Protective Measure against Beach Erosion at Yogyakarta, Indonesia

Abstract: Typically, the mitigation of coastal erosion is achieved by amending surface conditions using materials, such as concrete. The objective of this study is to evaluate the feasibility of constructing artificial beachrocks using natural materials (e.g., microbes, sand, shell, pieces of coral, and seaweed, etc.) within a short time, and to propose the method as a novel strategy for coastal protection. Initially, a survey on resistivity and a multichannel analysis of seismic waves (MASW) were conducted along the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Alternatively, the creation of artificial beachrocks using natural materials (e.g. microbes, sand, shell, pieces of coral and seaweed) within a short time by MICP method was a milder approach (Daryono et al, 2020; Imran et al, 2019).…”
Section: Promising Applications Of Micpmentioning
confidence: 99%
“…Alternatively, the creation of artificial beachrocks using natural materials (e.g. microbes, sand, shell, pieces of coral and seaweed) within a short time by MICP method was a milder approach (Daryono et al, 2020; Imran et al, 2019).…”
Section: Promising Applications Of Micpmentioning
confidence: 99%
“…Based on multidisciplinary research, MICP refers to utilizing microorganism function to induce the carbonate from urea to precipitate in the presence of calcium ions, filling the space in soils and bonding the loose particles to achieve Inspired by a natural phenomenon of microbial mineralization, applications of MICP have been expanding into a broader range over the past two decades. For instance, it can be an alternative to rigid structures using concrete for coastal erosion mitigation in the marine environment [8][9][10]. In terms of the construction industry, this technique is proved to have a promising future to be applied in soil improvement [11], liquefaction prevention [12], road construction [13], and slope stabilization [14].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by a natural phenomenon of microbial mineralization, applications of MICP have been expanding into a broader range over the past two decades. For instance, it can be an alternative to rigid structures using concrete for coastal erosion mitigation in the marine environment [ 8 , 9 , 10 ]. In terms of the construction industry, this technique is proved to have a promising future to be applied in soil improvement [ 11 ], liquefaction prevention [ 12 ], road construction [ 13 ], and slope stabilization [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies on using microbially induced calcite precipitation MICP and EICP for soil improvement, there are only a few MICP studies using this technique for the treatment of beach sand [16][17][18][19][20][21][22][23]. Shanahan and Montoya [16] created a bench model simulating a coastal sand dune using a clean fine sand, typical of coastal dune deposits.…”
Section: Introductionmentioning
confidence: 99%
“…The angle of repose of the treated sand increased remarkably as well. Daryono et al [22] studied the feasibility of constructing artificial beach rocks using MICP and beach sand as a proposed method for coastal protection against water erosion. The results indicated that artificial bedrocks have an unconfined compressive strength of up to around six MPa.…”
Section: Introductionmentioning
confidence: 99%